Implementation and Challenges of Problem Based Learning in Critical Thinking Skills in Elementary Schools: A Review of Pedagogic Competencies - Jayanto, Hendra Adi; Murwaningsih, Tri; Rukayah, Rukayah (Universitas Sebelas Maret, 2024)
This study describes the role of teachers in terms of teachers' pedagogical abilities in implementation and the obstacles experienced in applying problem-based learning models to critical thinking skills. Research focus: 1) identify teacher planning and implementation in the application of problem-based learning models on critical thinking skills in terms of pedagogic competence. 2) Describe the challenges faced by teachers and students in the application of critical thinking skills. 3) Solutions that can be done by teachers in implementing problem-based learning models on critical thinking skills. The research method used is descriptive qualitative with data collection techniques of interviews, observations, and documentation studies. The result of this study is that teachers in planning learning objectives in RPP have not contained critical skill indicators. Teachers can empower students' critical thinking skills, as facilitators teachers can improve classroom management skills to achieve learning goals. Group discussion forums can be an alternative solution to the challenges faced by teachers and students in optimize critical thinking skills. The conclusion of this study is that pedagogic competence has an effect on optimizing the application of problem-based learning models and critical thinking skills.